2022
DOI: 10.1038/s42005-022-01017-8
|View full text |Cite
|
Sign up to set email alerts
|

High cooperativity coupling to nuclear spins on a circuit quantum electrodynamics architecture

Abstract: Nuclear spins are candidates to encode qubits or qudits due to their isolation from magnetic noise and potentially long coherence times. However, their weak coupling to external stimuli makes them hard to integrate into circuit quantum electrodynamics architectures, the leading technology for solid-state quantum processors. Here, we study the coupling of 173Yb(III) nuclear spin states in an [Yb(trensal)] molecule to superconducting cavities. Experiments have been performed on magnetically dilute single crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…This could be done by employing a multimode resonator; it has been suggested that excitation bandwidths of 4 GHz could be possible . Alternatively, one could employ an architecture based on superconducting resonators, where frequencies differing by more than a factor of 7 have already been demonstrated . These devices typically operate in the few tens of GHz range .…”
Section: Discussionmentioning
confidence: 99%
“…This could be done by employing a multimode resonator; it has been suggested that excitation bandwidths of 4 GHz could be possible . Alternatively, one could employ an architecture based on superconducting resonators, where frequencies differing by more than a factor of 7 have already been demonstrated . These devices typically operate in the few tens of GHz range .…”
Section: Discussionmentioning
confidence: 99%
“…The inherent limitation of pulsing at multiple resonance frequencies to achieve the necessary entangled states may be realised using circuit quantum electrodynamic (QED) architectures, as applied recently to Yb(trensal) molecular spin qubits. [52] The weak dipolar interactions in the multi-qubit model system necessitate long pulses to implement the corresponding gate operations, however optimal control pulse shaping techniques may circumvent this by reducing the probability of unwanted transitions, even with fast pulses. [53] Moreover, stronger dipolar interactions obtained by chemically controlling the inter-qubit distance would not be detrimental to such a protocol as a result of the individually addressable gvalues of each spin qubit.…”
Section: Methodsmentioning
confidence: 99%
“…Transmission measurements detected the regime of high cooperative coupling (Ω > κ, γ) of resonator photons to both electron and nuclear spins. 80 The spectral map reflecting one of the nuclear spin transitions in 173 Yb(trensal) is shown in Figure 4i. Avoided crossing at around 17 mT is clearly visible, similar to the one in Figure 4d, while the driving frequency is one order of magnitude lower for nuclear spin transitions.…”
Section: Hybrid Msqds: Coupling Molecular Spins To Photons Of a Mw Re...mentioning
confidence: 99%